Analysis of the efficiency of the use of land resources within the boundaries of the Kodym territorial community of the Podil district of the Odessa region - Serbov, M.; Liashenko, G.; Danilova, N.; Volvach, O.; Nikitin, P. (Land Management, Cadastre and Land Monitoring, 2025)
Agricultural lands, as the most important element of national wealth and living conditions of society, within the Kodyma TG occupy 67.01% of the total area, which fully satisfies the needs of agricultural production of the community. However, the associated high degree of plowing leads to large-scale erosion processes and disrupts the general ecological balance in the area. The main way to preserve the ecological balance of the territory should be the transformation of plowed, degraded and low-productive arable lands into pastures, hayfields and afforestation of eroded slopes. Such transformation is also one of the ways to increase the area of forest land. Calculations were made of such indicators as agricultural development of the territory, plowing of the territory and plowing of agricultural lands. It was established that the area of agricultural lands occupies 65.4% of the territory of the Kodyma TG, and the TG belongs to the second group in terms of the degree of agricultural development. Agricultural lands have a fairly high level of plowing - 82.9% and are environmentally unstable. According to the results of calculations, it was found that the indicators of ecological stability of land use and the level of anthropogenic load are 0.4 and 3.89, respectively, and correspond to the assessment of the territory as weakly stable, with an increased level of anthropogenic load. Keywords: land resources, agricultural development, ecological stability, anthropogenic load.